2021
DOI: 10.1016/j.neubiorev.2021.05.028
|View full text |Cite
|
Sign up to set email alerts
|

The neuroscience of social feelings: mechanisms of adaptive social functioning

Abstract: Social feelings have conceptual and empirical connections with affect and emotion. In this review, we discuss how they relate to cognition, emotion, behavior and well-being. We examine the functional neuroanatomy and neurobiology of social feelings and their role in adaptive social functioning. Existing neuroscience literature is reviewed to identify concepts, methods and challenges that might be addressed by social feelings research. Specific topic areas highlight the influence and modulation of social feelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 337 publications
2
42
0
3
Order By: Relevance
“…, 2017 ). Importantly, while these circuits are not specific to attachment and support multiple affective processes of both social and non-social nature ( Eslinger et al. , 2021 ), research has repeatedly implicated these regions in the formation and maintenance of the parent-to-child attachment ( Swain et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 2017 ). Importantly, while these circuits are not specific to attachment and support multiple affective processes of both social and non-social nature ( Eslinger et al. , 2021 ), research has repeatedly implicated these regions in the formation and maintenance of the parent-to-child attachment ( Swain et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered a "pervasive and adverse psychological state with the feeling of emotional isolation state of being alone and separation from others" ( [20], p. 1). Such feeling may lead to increased mortality and other health risks [21]. For example, loneliness is linked to clinical diseases such as stroke and cardiovascular illness, and it is also a predictor of psychological symptoms such as depression, stress, and anxiety [22].…”
mentioning
confidence: 99%
“…Impacts of cognitive flexibility on inter-group conflicts, fear and bias. Recent studies support the notion that flexibility and cognitive empathy might be essential for alleviating social anxiety (Eslinger et al 2021;Clarke and Kiropoulos 2021). The brainimaging study of OFC-related anxiety showed that feelings of distress were maladaptively amplified when people misinterpreted the feelings, perspectives or intentions of others (Tei et al 2020).…”
Section: Discussionmentioning
confidence: 82%